John Dunbar - Stell, Geoffrey (Proceedings of the Society of Antiquaries of Scotland, 2018)
The reserved demeanour of the late John Greenwell Dunbar, OBE, MA, FSA, Honorary Fellow of the Society of Antiquaries of Scotland and of the Royal Incorporation of Architects in Scotland, belied the fact that he was a towering figure in the transformation of Scottish architectural scholarship in the second half of the 20th century, co-founder and doyen of the modern discipline in Scotland.